Fernando Ortiz: Caribbean and Mediterranean Counterpoints: Reseña de libro - Helmke Miquel, Ignacio (Notas de Antropología de las Américas, 2025)
Reseña de libro / Review of the book: Fernando Ortiz: Caribbean and Mediterranean Counterpoints. Stephan Palmié (ed.), 2023, Chicago: Hau Books, Open Access